The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s11892-007-0031-5
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive agents, insulin sensitivity, and new-onset diabetes

Abstract: The effects of the antihypertensive drugs on carbohydrate metabolism and the development of diabetes have been a major research field for more than two decades. Many clinical studies have investigated the effects of the antihypertensive classes on insulin sensitivity and glycemic control, whereas several observational studies and large outcome trials have examined associations of antihypertensive agents with diabetes incidence. In general, thiazide diuretics and conventional beta blockers decrease insulin sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 79 publications
1
24
0
Order By: Relevance
“…For more than two decades one of the most active area of research topics in the field of hypertension therapeutics was the possible effects of major antihypertensive drug classes on carbohydrate metabolism and the development of new-onset DM [ 14 ]. In this regard, numerous clinical studies have investigated the impact of antihypertensive agents on insulin sensitivity (IS) and glycemic control, whereas large outcome trials have explored the potential association between antihypertensive agents and incident DM.…”
Section: Choice Of Antihypertensive Treatment In Patients With Diabetmentioning
confidence: 99%
See 1 more Smart Citation
“…For more than two decades one of the most active area of research topics in the field of hypertension therapeutics was the possible effects of major antihypertensive drug classes on carbohydrate metabolism and the development of new-onset DM [ 14 ]. In this regard, numerous clinical studies have investigated the impact of antihypertensive agents on insulin sensitivity (IS) and glycemic control, whereas large outcome trials have explored the potential association between antihypertensive agents and incident DM.…”
Section: Choice Of Antihypertensive Treatment In Patients With Diabetmentioning
confidence: 99%
“…In this regard, numerous clinical studies have investigated the impact of antihypertensive agents on insulin sensitivity (IS) and glycemic control, whereas large outcome trials have explored the potential association between antihypertensive agents and incident DM. Another important issue is the possible harmful impact of antihypertensive therapyrelated new-onset DM on cardiovascular outcomes [ 14 ]; thus, presence of DM should be taken into consideration in the choice of the appropriate BP-lowering therapy in patients with hypertension and HF.…”
Section: Choice Of Antihypertensive Treatment In Patients With Diabetmentioning
confidence: 99%
“…RAAS blockers have beneficial effects on lipids and are thought to be protective or at least neutral for development of insulin resistance [13,52]. In a meta-analysis of 474 trials, ACE inhibitors decreased total cholesterol levels in patients with diabetes (but not LDL) and also decreased triglyceride levels, especially in patients with high baseline triglycerides [9].…”
Section: Raas Blockers: Ace Inhibitors and Arbsmentioning
confidence: 99%
“…5 Any medication that worsens insulin sensitivity, ie, thiazide diuretics or most ␤-blockers will hasten the development of diabetes mellitus in those with impaired fasting glucose. 6 Large observational studies demonstrate that thiazide diuretics and most ␤-blockers increase the incidence of new-onset diabetes mellitus compared with renin-angiotensin system (RAS) blockers or calcium channel blockers. 7 To further support this observation, a network-based meta-analysis of hypertensive agents showed that RAS blockers were the agents least likely to be associated with the development of diabetes mellitus, whereas thiazides had a higher incidence of diabetes mellitus compared with placebo.…”
mentioning
confidence: 99%